Liquid biopsy in bladder cancer: State of the art and future perspectives. (February 2022) - Crocetto, Felice; Barone, Biagio; Ferro, Matteo; Busetto, Gian Maria; La Civita, Evelina; Buonerba, Carlo; Di Lorenzo, Giuseppe; Terracciano, Daniela; Schalken, Jack A.
Graphical abstract: Highlights: The diagnosis of bladder cancer relies on cytology and cystoscopy. Cytology suffers from low sensibility while cystoscopy is burdened by discomfort, pain and infective complications. Liquid biopsy represents a novel technique that permits to diagnose, via biomarkers, cancer through body fluids. Urine allows the identification of several urinary biomarkers which could be used in bladder cancer diagnosis. This review aims to summarize the state of the art of this approach in urothelial cancer. Abstract: Bladder cancer is the most common malignancy of the urinary tract. Cystoscopy represents the gold standard in the diagnosis of suspicious bladder lesions. However, the procedure is invasive and burdened by pain, discomfort and infective complications. Cytology, which represents an alternative diagnostic possibility is limited by poor sensitivity. Considering the limitations of both procedures, and the necessity to perform multiple evaluations in patients who are in follow-up for bladder cancer, an improved non-invasive methodology is required in the clinical management of this disease. Liquid biopsy, e.g. the detection of clinical biomarkers in urine, represent a promising novel and non-invasive approach that could overcome those limitations and be integrated into the current clinical practice. The aim of this review is to summarize the state of the art of this approach and the latest novelties regarding detection, prognosis and surveillance of bladder cancer.